PENYULUHAN KESEHATAN DIABETES MELLITUS DAN IDENTIFIKASI RESIKO DIABETIK FOOT ULCER DI DUSUN BON JERUK WILAYAH KERJA PUSKESMAS AMPENAN TAHUN 2022 - Heny Marlina Riskawaty; Baik heny Rispawaty; Zaenal Arifin (Stikes Yarsi Mataram, 2022)
Diabetes Mellitus (DM) is a disease characterized by the occurrence of hyperglycemiaand disturbances of carbohydrate, fat, and protein metabolism associated with absoluteor relative deficiency of insulin action and/or secretion. Symptoms that people withDiabetes Mellitus complain about are polydipsia, polyuria, polyphagia, weight loss, andtingling. Diabetic foot ulcers are chronic complications arising from uncontrolledhyperglycemia, one of which is complications in the form of vascular disorders, chroniccomplications of diabetes mellitus in the form of open sores on the feet which can beaccompanied by local tissue death.The purpose of community service: is to identify theknowledge of the elderly about diabetes mellitus and identify the risk of developingdiabetic foot ulcers. The time required from preparation to implementation is 2 weeks.Respondents: All elderly people with a diagnosis of Diabetes Mellitus as many as 30people, participated in this activity until it was completed. The results identifiedknowledge of the elderly in a good category and from 30 elderly people 23 people wereidentified as having a risk of developing Diabetic foot ulcers. It is hoped that thePuskesmas can provide education about diet, physical activity and the use ofappropriate footwear to prevent the occurrence of Diabetic foot ulcers